2004
DOI: 10.1111/j.1439-0434.2003.00810.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Time of Spraying of Fungicide and Foliar Nutrient on Soybean Powdery Mildew

Abstract: With the objective of determining the effects of initial infection level (% leaf area infected, % l.a.i.) at the time of fungicide and foliar nutrient application for the control of powdery mildew, a study was carried out under greenhouse conditions at Embrapa Soja, Londrina, P.R. The fungicide tebuconazole (100 g a.i./ ha/application) and sulphur fungicide (2.0 kg a.i./ha/ application), sprayed at 20, 30, 40 and 50% l.a.i. (growth stages V3 and V5, between R5.1 and R5.3), and three applications (at V3, V4 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 6 publications
2
11
0
Order By: Relevance
“…Microsphaera diffusa)-is an important disease of soybeans, particularly in the United States, Paraguay, Brazil and Bolivia. However, this disease has only recently been observed in Australia [1][2][3][4][5][6]. The fungus is an obligate parasite and is characterised by white-grey mycelia and conidia growth which can be observed on all above-ground plant parts [1,6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Microsphaera diffusa)-is an important disease of soybeans, particularly in the United States, Paraguay, Brazil and Bolivia. However, this disease has only recently been observed in Australia [1][2][3][4][5][6]. The fungus is an obligate parasite and is characterised by white-grey mycelia and conidia growth which can be observed on all above-ground plant parts [1,6].…”
Section: Introductionmentioning
confidence: 99%
“…However, this disease has only recently been observed in Australia [1][2][3][4][5][6]. The fungus is an obligate parasite and is characterised by white-grey mycelia and conidia growth which can be observed on all above-ground plant parts [1,6]. During the early disease development stages, fine off-white or white fugal growth appears on the top surface of leaves [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated no significant increase in soybean yield with fungicide applications in the absence of disease [2023], while other studies suggested that yield increases can occur with foliar fungicide application even in the absence of disease [7, 2325]. Therefore, the economic return following a fungicide application does not intuitively follow a linear trend due to its apparent dependency on multiple factors such as disease pressure, class of fungicide being used (i.e., active ingredient), time of application (growth stage of the plant), and environmental conditions [19, 26, 27].…”
Section: Introductionmentioning
confidence: 99%
“…Author(s) agree that this article remain permanently open access under the terms of the Creative Commons Attribution License 4.0 International License (Soro et al, 2015). Many producers make more and more use of liquid organic fertilization due to these constraints (William et al, 2004;Yorinori et al, 2004). These producers act thus, in the direction of improving the soil fertility and allowing a better availability of the soil nutrients for the plant, in order to guarantee a better productivity.…”
Section: Introductionmentioning
confidence: 99%